Diversity of endogenous avian leukosis virus subgroup E (ALVE) insertions in indigenous chickens - Mason, A.S.; Miedzinska, K.; Kebede, A.; Bamidele, Oladeji; Al-Jumaili, A.S.; Dessie, Tadelle; Hanotte, Olivier H.; Smith, J. (Springer, 2020)
Avian leukosis virus subgroup E (ALVE) insertions are endogenous retroviruses (ERV) that are restricted to the domestic chicken and its wild progenitor. In commercial chickens, ALVE are known to have a detrimental effect on productivity and provide a source for recombination with exogenous retroviruses. The wider diversity of ALVE in non-commercial chickens and the role of these elements in ERV-derived immunity (EDI) are yet to be investigated.In total, 974 different ALVE were identified from 407 chickens sampled from village populations in Ethiopia, Iraq, and Nigeria, using the recently developed obsERVer bioinformatics identification pipeline. Eighty-eight percent of all identified ALVE were novel, bringing the known number of ALVE integrations to more than 1300 across all analysed chickens. ALVE content was highly lineage-specific and populations generally exhibited a large diversity of ALVE at low frequencies, which is typical for ERV involved in EDI. A significantly larger number of ALVE was found within or near coding regions than expected by chance, although a relative depletion of ALVE was observed within coding regions, which likely reflects selection against deleterious integrations. These effects were less pronounced than in previous analyses of chickens from commercial lines.Identification of more than 850 novel ALVE has trebled the known diversity of these retroviral elements. This work provides the basis for future studies to fully quantify the role of ALVE in immunity against exogenous ALV, and development of programmes to improve the productivity and welfare of chickens in developing economies.